Unsteady MHD Non-Darcian Flow over a Vertical Stretching Plate Embedded in a Porous Medium with Thermal Non-Equilibrium Model (Advances in Applied Mathematics and Mechanics, 2018)
An analysis is performed to study the influence of local thermal non-equilibrium(LTNE) on unsteady MHD laminar boundary layer flow of viscous, incompressiblefluid over a vertical stretching plate embedded in a sparsely packed porousmedium in the presence of heat generation/absorption. The flow in the porous mediumis governed by Brinkman-Forchheimer extended Darcy model. A uniform heatsource or sink is presented in the solid phase. By applying similarity analysis, thegoverning partial differential equations are transformed into a set of time dependentnon-linear coupled ordinary differential equations and they are solved numerically byRunge-Kutta Fehlberg method along with shooting technique. The obtained resultsare displayed graphically to illustrate the influence of different physical parameters onthe velocity, temperature profile and heat transfer rate for both fluid and solid phases.Moreover, the numerical results obtained in this study are compared with the existingliterature in the case of LTE and found that they are in good agreement.